Multiprocessor technologies of design for tasks of Monte – Karlo - Швачич, Геннадий Григорьевич (Eastern-European Journal of Enterprise Technologies, 2013)
The process of mathematical modeling of applied Monte-Carlo problems based on the use of multiprocessor computation system found further development in the paper. Operating experience of the first parallel systems has shown that their efficiency requires radical change of the structure of numerical methods. In this connection, the corresponding distributed algorithms were developed, the features of modeling applied problems based on multi-processor systems were identified and shown. Application of the developed approach provides a new way to consider the idea of computation parallelization and the use of cluster computation technologies. A modified algorithm for parallel computation using the Monte-Carlo method is proposed in the paper. Here, each computer has its own random number generator. In this case, the intermediate computations are carried out independently on different, individual cluster blades - “computers”, and the results are processed at any individual master-blade - “analyzer”. This allows to get rid of the indispensable presence of routercommunicator between the random number generator and “computer”. Obviously, this solution allows speeding up the computational process. The computational schemes that enhance the productivity and performance are given. The effectiveness of the proposed approach is illustrated by a comparative analysis of solution of some class of problems